The Role of the Ambon City’s Population and Civil Registration Office in Controlling Incoming Migration - Rahmawati Sururama; Tiara Nanuru (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The objectives of this study are to find out the role of the Ambon City’s Population and Civil Registration Office in Controlling Incoming Migration and to find out the obstacles faced by the Ambon City's Population and Civil Registration Office in Controlling Incoming Migration. This study used a qualitative descriptive research method. Data Collection was obtained through observation, interview, and documentation. Data were analyzed using data reduction, display data, and verification. Primary and secondary data were used as the sources for analysis. The informants in this study were the chief of the Population and Civil Registration Office Ambon City and the Population Monitoring and Control Division, as well as the migrants. Ambon City’s Government, through the Population and Civil Registration Office, has carried out its duties as regulated by the Mayor of Ambon Regulation No. 17/ 2009 article 14 paragraph 2, namely: Coordinating the monitoring of urbanization of population and supervising the registration of population mobility flows. The constraints faced by the Ambon City population and civil registration office, namely: Most of the population who migrated to Ambon City did not report themselves so the authorities had difficulty monitoring the flow of urbanization and monitoring population mobility; inspected and supervised residents, who have not lived in Ambon city for six months, have moved to other areas; there is no effort and awareness of people who have been examined and under supervision to change by reporting personal data to the government.